SB5 shows cross-immunogenicity to adalimumab but not infliximab: results in patients with inflammatory bowel disease or rheumatoid arthritis - Joao Goncalves; Gihyun Myung; MinJeong Park; Deokyoon Jeong; Jeehoon Ghil (Therapeutic Advances in Gastroenterology, 2019)
Background: The primary objective of this study was to analyze the cross-reactivity of antidrug antibodies to reference adalimumab (ADL) and SB5 (adalimumab biosimilar) in patients with inflammatory bowel disease (IBD) or rheumatoid arthritis (RA). Methods: Sera from patients with IBD and RA with or without antibodies to adalimumab (ATA+ or ATA–, respectively) were tested for cross-reactivity with SB5 and ADL. Functional inhibition of tumor necrosis factor-α binding was measured. Sera from patients with antibodies to reference infliximab (ATI+) were examined for cross-reactivity to SB5. Sera were tested by enzyme-linked immunosorbent assay. Results: All 30 anti-ADL ATA+ sera from patients with IBD and all 4 anti-SB5 ATA+ sera from patients with RA were cross-reactive with ADL and SB5 (range of mean concentrations: IBD, 20.99–21.31 μg/ml; RA, 16.46–17.48 μg/ml). In general, there was no significant difference between mean ATA titers. A strong correlation was detected in all ATA+ samples (rho = 0.997 to >0.999; p  < 0.001 each). However, ATA– sera were not reactive to either ADL or SB5. anti-ADL ATA+ sera similarly neutralized functional activity of ADL and SB5; no functional inhibition was observed with ATA– sera. ATI+ sera did not cross-react with SB5. Conclusions: ADL and SB5 show cross-immunogenicity in sera from patients with IBD or RA, supporting shared immune-dominant epitopes. ATI+ sera did not cross-react with SB5, suggesting different immunogenic epitopes between infliximab and SB5.